Prove that sinα + sinβ + sinγ − sin(α + β+ γ) = 4sin(α+β/2)sin(β+γ/2)sin(α+γ/2)
Answers
Answer:
sinα + sinβ + sinγ − sin(α + β+ γ) = 4 Sin((α + β)/2)Sin((β + γ)/2)Sin((α + γ)/2)
Step-by-step explanation:
sinα + sinβ + sinγ − sin(α + β+ γ) = 4sin(α+β/2)sin(β+γ/2)sin(α+γ/2)
Using SinA + SinB = 2Sin((A + B)/2)Cos((A - B)/2)
SinA - SinB = 2Sin((A - B)/2)Cos((A + B)/2)
LHS = sinα + sinβ + sinγ − sin(α + β+ γ)
= 2Sin((α + β)/2)Cos((α - β)/2) + 2 Sin((-α - β)/2)Cos((α + β+ 2γ)/2)
Using Sin(-A) = - SinA
= 2Sin((α + β)/2)Cos((α - β)/2) -2 Sin((α + β)/2)Cos((α + β+ 2γ)/2)
= 2Sin((α + β)/2) (Cos((α - β)/2) - Cos((α + β+ 2γ)/2)
Using CosA - CosB = -2Sin((a + b)/2)Sin((a-b)/2)
= 2Sin((α + β)/2) ( -2 Sin((α + γ)/2)Sin((-β - γ)/2)
= 2Sin((α + β)/2) ( -2 Sin((α + γ)/2) (-Sin((β + γ)/2))
= 4 Sin((α + β)/2)Sin((β + γ)/2)Sin((α + γ)/2)
= RHS
QED
Proved